Effect of sodium nitrite, sodium chloride, sodium erythorbate, and sodium tripolyphosphate on nontoxigenic Clostridium botulinum LNT01 and C. sporogenes in growth medium and cooked cured beef – Development and validation of critical control surface - Ahmad, Nurul Hawa; Huang, Lihan; Hwang, Cheng An (Elsevier, 2025)
Clostridium botulinum is a serious foodborne pathogen that can complicate the safety of cooked meats. This study was conducted to evaluate the effect of sodium chloride (NaCl, 1–3 %), sodium nitrite (NaNO2, 100–200 ppm), sodium erythorbate (SE, 0–547 ppm), and sodium tripolyphosphate (STPP, 0–0.5 %), 27 treatments in total, on the spores of two non-toxigenic clostridial surrogates, including C. botulinum LNT01 and C. sporogenes PA 3679. The surrogates were inoculated to fortified Shahidi Ferguson Perfringens (SFP) agar formulated with different combinations of NaCl, NaNO2, SE, and STPP in 96-well microplates and then exposed to simulated curing, cooking, and incubation at 37 °C to observe the bacterial growth. Logistic regression models were developed to define critical control surfaces (CCS) to prevent the growth of C. botulinum in cured meats. Validation of CCS was performed against C. botulinum LNT01 using 4 pre-selected conditions in cooked cured ground beef. STPP, previously found very effective in controlling C. perfringens, supported the growth of both surrogates, but growth was significantly inhibited by NaNO2 and NaCl. However, C. sporogenes PA 3679 was more difficult to control than C. botulinum LNT01. The validation of the CCS for C. botulinum LNT01 showed an accuracy of 89.8 % in cooked, cured ground beef. The results of this study suggested that the CCS could be used to properly formulate cured meat products to reduce the risk of foodborne botulism.